TRANSLATION METHODS AND QUALITY OF IDIOMATIC EXPRESSION IN MY SISTER’S KEEPER MOVIE - Wijaksono, Rizki Nugroho; Hilman, Evert Haryanto; Mustolih, Ahmad (BASIS (Bahasa dan Sastra Inggris), 2022)
This research analyzed idiomatic expressions in My Sister’s Keeper movie based on Newmark’s theory. This research aimed to identify the types of translation methods in translating idiomatic expression and the quality of translation based on Nababan’s theory used in translating idiomatic expression found in My Sister’s Keeper movie. This research used descriptive qualitative method. The data were collected through documentation because the data were taken from the dialogues of the transcript in My Sister’s Keeper movie. The result of this research showed that there were 109 data which contain types of translation methods applied in idiomatic expressions, which were; word-for-word translation with 14 data (13%), literal translation with 18 data (16%), faithful translation with 9 data (8%), semantic translation with 12 data (11%), adaptation translation with 5 data (5%), free translation with 3 data (3%), idiomatic translation with 29 data (27%), and communicative translation with 19 data (17%). Afterward, the raters indicated the result of the translation quality assessment showed that 12 data were scored less accurate and 4 less acceptable, all in all, other data showed a high-level accuracy, acceptability, and readability. The most frequently types of translation method were idiomatic translation because idiomatic translation more commonly used in idiomatic expression which to distorted nuances of meaning by preferring colloquialisms.